Growing Impact of Carbohydrate‐Based Organocatalysts. Issue 19 (16th May 2022) - Singh, Sumit K.; Mishra, Nidhi; Kumar, Sunil; Jaiswal, Manoj K.; Tiwari, Vinod K.
Abstract: Organocatalysis has emerged as one of the most progressive and prevailing field of organic synthesis to assist green chemistry. Constantly increasing demand of promising scaffolds to develop potent organocatalysts has impelled researchers to utilize the unique traits of carbohydrate moiety in this field. Biological significance of carbohydrates, as well as, their high natural abundance as chiral non‐racemic material, presence of multiple hydroxyl groups, several stereogenic centres, and easily modifiable structure make this moiety an appropriate skeleton to develop organocatalysts to enhance productivity and selectivity of a chemical transformation. 21 st Century has witnessed the progress of carbohydrate moiety in development of organocatalysts from obscurity to eminence. This review encapsulates the importance of carbohydrate scaffolds in organocatalysis mainly dealing with the synthesis and applications carbohydrate‐derived organocatalyst in different common organic reactions with their significance and future purspectives. Abstract : There is an increased demand of promising organacatalysts for the efficient and stereselective catalysis of diverse range of organic reactions to driven biologically relevant candidates under environmental benign condition. Carbohydrates, a most abundant natural product are chiral, functional, cheap, and biocompatible entities have potential utility to serve as suitable organocatalysts to enhance the selectivity of chemical reactions. This tutorial review highlights the synthesis of carbohydrate‐based organocatalysts and their growing impact in various stereoselective reactions.